Observation of Nutritional Status in Adolescents with HIV/AIDS - Erika Martining Wardani; Riezky Faisal Nugroho (WMJ (Warmadewa Medical Journal), 2023)
Adolescents with HIV/AIDS (Human Immunodeficiency Virus - Acquired Immunodeficiency Syndrome) continue to increase every year in line with the increase in sex behavior outside of marriage. One of the problems in adolescents with HIV / AIDS is malnutrition status. The purpose of the study was to observe nutritional status in adolescents with HIV / AIDS. The subjects were all adolescents with HIV/AIDS at the Kompeda Surabaya Foundation. The research design in this study is a time series, measuring nutritional status variables at some time using weight parameters according to age. Data collection was carried out on February-April 2022. The measurements were conducted using a bathroom scale. The number of subjects was 150 people with incidental sampling techniques. Inclusion criteria: adolescents diagnosed with HIV/AIDS, living in shelters, allowed by caregivers, ages 12-21, not being hospitalized during the study. Exclusion criteria: died, did not follow complete weight monitoring. During the study none of the subjects resigned nor were excluded from the study. The results of the study found that 90 had normal nutritional status and 60 were abnormal. There is a statistically significant difference in nutritional status between the first and second measurements. Foundation managers need to make efforts by paying more attention to adolescent nutritional intake so that nutritional status can improve.